Study on the preparation and performances analysis of lightweight high strength ceramsite aerated concrete - Peng Liu; Ao Luo; Lei Liu; Yongling Li; Sanling Zhang; Weiting Zhi; Dong Pan; Ying Chen; Zhiwu Yu (Journal of Materials Research and Technology, 2023)
An orthogonal test of the component design of aerated concrete was carried out to solve the problems of low strength, easy cracking, and high water absorption of aerated concrete. The influences of cement content, water-binder ratio, foaming agent content, and polypropylene fiber content on the performances of aerated concrete including dry density, compressive strength, and thermal conductivity were investigated. Furthermore, the optimal composition of aerated concrete was determined. The test results showed that the dry density, compressive strength, thermal conductivity, and water absorption of aerated concrete were greatly influenced by the dosage of the foaming agent. Additionally, the water-binder ratio was found to significantly influence the apparent porosity of aerated concrete. Based on the experiment, the optimal combination of components for aerated concrete was 65 wt.% cement and 35% wt.% mineral admixture with a fly ash to slag ratio of 3:1. Meanwhile, the content of water-binder ratio, foaming agent, and polypropylene fibers were 0.4, 4 wt.%, and 0.4 wt.% of the total cementitious material, respectively. Among the mix proportions in this study, aerated concrete prepared by using the above mix proportion had the best performances. Subsequently, the influence of ceramsite content on the strength, dry density, and thermal conductivity of aerated concrete was analyzed. The results showed that the dry density and thermal conductivity of ceramsite aerated concrete increased with the increase of ceramsite content, but the change law of the water absorption was the opposite. Moreover, the compressive strength increased first and then decreased with the increase of ceramsite content, while the apparent porosity was the opposite. The optimal ceramsite content in ceramsite aerated concrete was 20 wt.%.